2020
DOI: 10.1038/s41598-020-58634-y
|View full text |Cite
|
Sign up to set email alerts
|

Inferring quantity and qualities of superimposed reaction rates from single molecule survival time distributions

Abstract: Actions of molecular species, for example binding of transcription factors to chromatin, may comprise several superimposed reaction pathways. The number and the rate constants of such superimposed reactions can in principle be resolved by inverse Laplace transformation of the corresponding distribution of reaction lifetimes. However, current approaches to solve this transformation are challenged by photobleaching-prone fluorescence measurements of lifetime distributions. Here, we present a genuine rate identif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 46 publications
1
46
0
Order By: Relevance
“…We then accumulated the binding times of each time-lapse condition in survival time distributions (Figure 2B and Figure S4). Next, we extracted the dissociation rate spectra of TALE-TFs using genuine rate identification (GRID) (Figure 2B, 2C and S4) 53 . GRID yields the dissociation rate spectrum by inverse Laplace transformation of survival time distributions and enables correcting for photobleaching by global consideration of all time-lapse conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We then accumulated the binding times of each time-lapse condition in survival time distributions (Figure 2B and Figure S4). Next, we extracted the dissociation rate spectra of TALE-TFs using genuine rate identification (GRID) (Figure 2B, 2C and S4) 53 . GRID yields the dissociation rate spectrum by inverse Laplace transformation of survival time distributions and enables correcting for photobleaching by global consideration of all time-lapse conditions.…”
Section: Resultsmentioning
confidence: 99%
“…We determined the dissociation rate spectrum of bound TALE-TF by analysing the fluorescence survival time distributions obtained from time-lapse imaging with GRID 53 . In brief, GRID performs an inverse Laplace transformation of a fluorescence survival time distribution to reveal the underlying dissociation rate spectrum.…”
Section: Methodsmentioning
confidence: 99%
“…Using interlaced time-lapse microscopy (ITM) (Reisser et al, 2018), we observed that 87% of MVI molecules were fast diffusing, whereas 13% were static, probably corresponding to chromatin bound molecules (Figure 1f and Methods). In these experiments, we defined a molecule to be bound if it was confined to a radius of 160 nm for at least 100 ms. We next identified dissociation rates of bound MVI molecules from chromatin using time-lapse microscopy (Gebhardt et al, 2013) to correct for photobleaching and genuine rate identification (GRID), which allows extracting a complete spectrum of dissociation rates from single molecule fluorescence survival time distributions (Figure 1g, Supplementary Figure 2 and Methods) (Reisser et al, 2020). (Reisser et al, 2020) using all data (magenta).…”
Section: Nuclear Myosin VI Exhibits Different Kinetic Fractions and Umentioning
confidence: 99%
“…In these experiments, we defined a molecule to be bound if it was confined to a radius of 160 nm for at least 100 ms. We next identified dissociation rates of bound MVI molecules from chromatin using time-lapse microscopy (Gebhardt et al, 2013) to correct for photobleaching and genuine rate identification (GRID), which allows extracting a complete spectrum of dissociation rates from single molecule fluorescence survival time distributions (Figure 1g, Supplementary Figure 2 and Methods) (Reisser et al, 2020). (Reisser et al, 2020) using all data (magenta). Error estimation was obtained by resampling with 80% of the data (blue)(Methods).…”
Section: Nuclear Myosin VI Exhibits Different Kinetic Fractions and Umentioning
confidence: 99%
See 1 more Smart Citation